E. A. KYSIL’OVA: STUDY OF COLOR NAMES WITHIN THE COURSE «UKRAINIAN AS A FOREIGN LANGUAGE» (etymological aspect) - KYSIL’OVA, E. A. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. A person perceives most information through sight. The world around us is full of shapes, sizes and colors, distinguishing them we learn the environment, describe it. That is why during the study of a foreign language one of the first thematic blocks is a block of color names, or coloratives, i. e. lexical-semantic group of words denoting colors. In the context of studying this group of words, it becomes necessary to acquaint foreign students with at least the basic concepts of the Ukrainian word formation. It is necessary to find creative bases for both primary and secondary color names in the Ukrainian language, and this encourages the active use of dictionaries of different types, in this case the leading dictionaries will be etymological and historical-etymological ones. Purpose. The aim of the study is to try to consider the colors of the Ukrainian language as a striking example of a lexical-semantic group, the formation of which is closely related to the peculiarities of the Ukrainians’ perception of the environment. At the same time, it is on the example of the formation of the Ukrainian color names there is a visual demonstration of the search for the creative bases for the Ukrainian words. Results. The course «Ukrainian as a Foreign Language» focuses on the accuracy of translation and search for the most appropriate foreign language equivalents for the Ukrainian color names in the languages spoken by foreign students, and on the symbolic component of colors in different cultures. It is also noted that the absence of certain phenomena, concepts, objects in a particular culture and life of a country affects the formation of the lexical block associated with the naming of colors and shades, the presence of which in the Ukrainian language in this case requires additional comment from a teacher. The etymology of such basic color names of the Ukrainian language as червоний and синій and their peripheral color names are studied as illustrative examples. Emphasis is placed on the existence of numerous names of shades in the Ukrainian language in relation to the mentioned primary colors, the presence of which indicates a very subtle perception of color in our culture, because the slightest change in color intensity or brightness becomes noticeable and requires a separate clarifying name. At the same time, the question of the existence of groups of secondary color names, motivated by objects of animate and inanimate nature, arises. Scientific novelty of the research results. Within the course «Ukrainian as a foreign language» an attempt is made to consider the search for creative bases for the Ukrainian words through the etymological analysis of the main and peripheral color names in the Ukrainian language. Conclusions. The analysis of the origin of the main and peripheral colorants in the Ukrainian language presented in the article not only demonstrates the richness of the Ukrainian vocabulary and figurative worldview of the Ukrainians, but also promotes the active search for creative words for color names by foreign students and the ways of their creation.